National Concept of Development of Vaccine Prophylaxis in Russia - N. I. Briko; I. V. Feldblyum (Эпидемиология и вакцинопрофилактика)
The article is dedicated to outlining the conceptual directions for the development of vaccination in the Russian Federation. The provisions of the concept are formulated based on the authors' years of research on vaccination issues and analysis of data from domestic and foreign scientific literature. The main provisions of the concept aim at strengthening the state policy in the field of vaccination, reconstructing and expanding enterprises for the production of domestic vaccines, developing and improving immunobiological medicinal products against current infections, refining the National Immunization Schedule and Vaccination Schedule according to epidemiological indications; further promoting the WHO's "lifelong immunization" strategy; developing regional immunization programs; implementing a risk-oriented approach in the development of immunization programs; developing a system for monitoring post-vaccination complications; implementing epidemiological surveillance of vaccination as a methodology for assessing the strategy and tactics of immunization in accordance with the epidemiological situation; ensuring commitment to vaccination among the population, healthcare workers, and legislative and executive authorities.